Synthesis of biomass-derived bottom waste ash based rigid biopolyurethane composite foams: Rheological behaviour, structure and performance characteristics. (February 2019) - Kairytė, Agnė; Kizinievič, Olga; Kizinievič, Viktor; Kremensas, Arūnas
Abstract: This paper reports a novel type of rigid biopolyurethane composite foam based on rapeseed oil polyol and biomass-derived bottom waste ash (WA) for thermal insulation applications. It is shown that biopolyol premixes with various amounts of WA are characterised by a slightly increased dynamic viscosity, from 115 mPa·s to 289 mPa·s. Moreover, WA particles absorb part of the heat generated from the reaction and reduce the temperature by 31 °C, thus inhibiting the string-gel and tack-free times. The WA particles makes them possible nucleation sites. Therefore the average cell size reduce by an average of 2.4 times and thermal conductivity when measured 1 day after production – by approximately 3.6% compared to the control foam. Furthermore, moisture-mechanical properties show that WA increases water absorption due to the unburnt carbon in the WA. The slightly reduced closed cell content increases the compressive strength by ∼14% when 20 wt% of WA is used.